2004
DOI: 10.1023/b:bigi.0000012143.48298.71
|View full text |Cite
|
Sign up to set email alerts
|

AFLP-Based Genetic Diversity and Its Comparison with Diversity Based on SSR, SAMPL, and Phenotypic Traits in Bread Wheat

Abstract: Data on AFLP (eight primer pairs) and 14 phenotypic traits, collected on 55 elite and exotic bread wheat genotypes, were utilized for estimations of genetic diversity. We earlier used these 55 genotypes for a similar study using SSRs and SAMPL. As many as 615 scorable AFLP bands visualized included 287 (46.6%) polymorphic bands. The phenotypic traits included yield and its component traits, as well as physiomorphological traits like flag leaf area. Dendrograms were prepared using cluster analysis based on Jacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 45 publications
5
37
0
4
Order By: Relevance
“…A study based on 200 polymorphic bands obtained from fi ve AFLP primer combinations was reported (Corbellini et al, 2002). However, polymorphism levels as low as 47% have also been detected in wheat (Roy et al, 2004). These reports confi rm that AFLP markers can be effi ciently used to detect genetic variability in wheat.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…A study based on 200 polymorphic bands obtained from fi ve AFLP primer combinations was reported (Corbellini et al, 2002). However, polymorphism levels as low as 47% have also been detected in wheat (Roy et al, 2004). These reports confi rm that AFLP markers can be effi ciently used to detect genetic variability in wheat.…”
Section: Resultsmentioning
confidence: 66%
“…Some studies on wheat have reported the association between hybrid performance and morphological (Cruz et al, 2004), molecular (Roy et al, 2004), combined morphological and molecular (Franco et al, 2001;Vieira et al, 2007), and pedigree-based distances (Almanza-Pinzón et al, 2003). Such tools are important auxiliary techniques for the selection of the best parental combinations and for a more rational use of germplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grouping of genotypes reveled that indentified tolerant genotypes may be used as donor in various hybridization programmes to improve yield under sodic soil created saline stress environment. Earlier studied have also reported substantial genetic divergence in wheat (Deshmukh et al, 1999;Roy et al, 2004;Verma et al, 2006;Singh et al, 2006;Iqubal et al, 2007). The cluster pattern of the genotypes showed non-parallelism between geographic and genetic diversity (Singh et al, 2009).…”
Section: Resultsmentioning
confidence: 94%
“…Earlier studied have also reported substantial genetic divergence in wheat (Deshmukh et al, 1999;Roy et al, 2004;Verma et al, 2006;Singh et al, 2006;Iqubal et al, 2007). The grouping of genotypes reveled that indentified tolerant genotypes may be used as donor in various hybridization programmes to improve yield under sodic soil created saline stress environment.…”
Section: Resultsmentioning
confidence: 97%